Association of knee pain and different definitions of knee osteoarthritis with health-related quality of life: a population-based cohort study in southern Sweden. Issue 1 (December 2016) - Kiadaliri, Aliasghar; Lamm, Carl; de Verdier, Maria; Engström, Gunnar; Turkiewicz, Aleksandra; Lohmander, L.; Englund, Martin
Abstract Background While the impact of knee pain and knee osteoarthritis (OA) on health-related quality of life (HRQoL) has been investigated in the literature, there is a lack of knowledge on the impact of different definitions of OA on HRQoL. The main aim of this study was to measure and compare the impact of knee OA and its different definitions on HRQoL in the general population. Methods A random sample of 1300 participants from Malmö, Sweden with pain in one or both knees in the past 12 months with duration ≥4 weeks and 650 participants without were invited to clinical and radiographic knee examination. A total of 1527 individuals with a mean (SD) age 69.4 (7.2) participated and responded to both generic (EQ-5D-3L) and disease-specific (the Knee injury and Osteoarthritis Outcome Score) questionnaires. Knee pain was defined as pain during the last month during most of the days. Knee OA was defined radiographically (equivalent to Kellgren and Lawrence grade ≥2) and clinically according to the American College of Rheumatology (ACR) criteria. Results Of participants with either knee pain or knee OA or both, 7 % reported no problem for the EQ-5D-3L attributes. The corresponding proportion among references (neither knee pain nor OA) was 42 %. The participants with knee pain and OA had all HRQoL measures lower compared to those with knee pain butno OA. The ACR clinical definition of knee OA was associated with lower HRQoL than the definition based on radiographic knee OA (adjusted difference −0.08 in UK EQ-5D-3L index score). Conclusions Applying different definitions of knee OA result in different levels of HRQoL and this is mainly explained by the knee pain experience. These differences may lead to discrepant conclusions from cost-utility analyses.